Development and application of high resolution mass spectrometry analytical method to study and identify the photoinduced transformation products of environmental pollutants. (15th April 2022) - Dal Bello, Federica; Mecarelli, Enrica; Aigotti, Riccardo; Davoli, Enrico; Calza, Paola; Medana, Claudio
Abstract: Terpenes are among the major causes of pleasant or unpleasant odors close to active or inactive landfills. We studied R-limonene and p-cymene environmental degradation products using the heterogeneous photocatalysis mediated by titanium dioxide to explore the odor pollution. The aim of the study was the development of mass spectrometry based methods both hyphenated with GC and HPLC to identify and characterize transformation products (TPs) derived from photodegradation of R-limonene and p-cymene. With the GC-MS method we identified three TPs for R-limonene and two for p-cymene comparing the obtained mass spectra with those in the NIST library. While with HPLC-MS method, thanks to the use of the high resolution of MS tool, we recognized four and five TPs for R-limonene and p-cymene respectively. No p-cymene was detected as R-limonene transformation product. The methods developed were then applied to real environmental samples coming from landfills active (Lan1) or inactive (Lan2 and Lan3) located in northern Italy. R-limonene was detected in the active landfill (Lan1 at the concentration of 2.35 μg/mL) together with one of its TPs and one TP derived from p-cymene. p-Cymene was detected in the other two inactive landfills (Lan2 and Lan3 concentrations 0.025 and 0.15 μg/mL, respectively) together with one of its TP and two TPs coming from R-limonene photodegradation. The finding of TPs together with R-limonene and p-cymene both in active and inactive landfills point out the attention on the reduction of these molecules in the environment to reduce pollution and human risks. Highlights: Terpenes were associated to odor pollution in the environment close to landfills. Degradation of molecules in landfills is both anaerobic and aerobic (oxidation). Photodegradation induced by TiO2 was used to simulate species oxidation in laboratory. GC-HPLC/MS methods were developed to identify TPs of R-limonene and p-cymene. Methods were applied to real samples from landfills and TPs were quantified.